2009
DOI: 10.1017/s0967199409005279
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of histone acetylation by trichostatin A duringin vitrofertilization of bovine oocytes affects cell number of the inner cell mass of the resulting blastocysts

Abstract: Histone acetylation is one of the major mechanisms of epigenetic reprogramming of gamete genomes after fertilization to establish a totipotent state for normal development. In the present study, the effects of trichostatin A (TSA), an inhibitor of histone deacetylase, during in vitro fertilization (IVF) of bovine oocytes on subsequent embryonic development were investigated. Cumulus-enclosed oocytes obtained from slaughterhouse bovine ovaries were matured in vitro and subjected to IVF in a defined medium suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…It is likely that the pattern of histone acetylation at the four-cell stage is associated with those changes found in this study (Figs 3 and 4). This inference is further supported by Ikeda et al (2009), whose report showed that epigenetic modifications to the genome during fertilization exerted a carryover effect on cell proliferation and differentiation of preimplantation embryos. Furthermore, the level of POU5F1 protein expression would be critical to ZPF42 expression due to a POU/octamer site found in its promoter region (Cervera et al 2009).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…It is likely that the pattern of histone acetylation at the four-cell stage is associated with those changes found in this study (Figs 3 and 4). This inference is further supported by Ikeda et al (2009), whose report showed that epigenetic modifications to the genome during fertilization exerted a carryover effect on cell proliferation and differentiation of preimplantation embryos. Furthermore, the level of POU5F1 protein expression would be critical to ZPF42 expression due to a POU/octamer site found in its promoter region (Cervera et al 2009).…”
Section: Discussionmentioning
confidence: 68%
“…In contrast to POU5F1 and CDX2, ZPF42, a developmentally regulated gene containing zinc finger motifs (Hosler et al 1989), was expressed at a higher level in the SHH-treated embryos, although the exact function and mechanisms are not clear. This might have altered the ratio of inner cell mass to trophectoderm cells at the blastocyst stage, given that enhanced histone acetylation led to reallocation of the ICM and TE cells in bovine blastocysts (Cervera et al 2009, Ikeda et al 2009). It is likely that the pattern of histone acetylation at the four-cell stage is associated with those changes found in this study (Figs 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…Kwun et al reported that the action of glucose mainly stimulated blastomere differentiation into ICM cells, as evidenced by an increased number of ICM cells and an increased ratio of ICM to TE cells in blastocysts (Kwun et al 2003). Ikeda et al reported that the addition of trichostatin A, an inhibitor of histone deacetylase, to the insemination medium increased the ICM cell number, but not the TE cell number, by affecting the epigenetic acetylation of gamete genomes (Ikeda et al 2009). In the present study, the ICM cell number in the blastocysts developed using sericin was significantly more than that in the blastocysts developed in vivo and using FBS, although the total cell number in the blastocysts developed using sericin was similar to that in the those developed in vivo and significantly fewer than those developed using FBS.…”
Section: Discussionmentioning
confidence: 99%
“…Cleavage rate and blastocyst formation were not altered. However, there were more cells in the ICM of embryos that received TSA during fertilization [104]. These results suggest that alteration of histone acetylation during fertilization affects subsequent cell proliferation and differentiation [104].…”
Section: The Use Of Histone Deacetylase Inhibitors For In Vitro Prmentioning
confidence: 99%
“…However, there were more cells in the ICM of embryos that received TSA during fertilization [104]. These results suggest that alteration of histone acetylation during fertilization affects subsequent cell proliferation and differentiation [104]. Embryos cultured with TSA after fertilization, in an effort to aid the activation of embryo genome, had increased levels of histone acetylation, but blastocyst development was not affected [99].…”
Section: The Use Of Histone Deacetylase Inhibitors For In Vitro Prmentioning
confidence: 99%